If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(13+2x)(11+2x)=217
We move all terms to the left:
(13+2x)(11+2x)-(217)=0
We add all the numbers together, and all the variables
(2x+13)(2x+11)-217=0
We multiply parentheses ..
(+4x^2+22x+26x+143)-217=0
We get rid of parentheses
4x^2+22x+26x+143-217=0
We add all the numbers together, and all the variables
4x^2+48x-74=0
a = 4; b = 48; c = -74;
Δ = b2-4ac
Δ = 482-4·4·(-74)
Δ = 3488
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{3488}=\sqrt{16*218}=\sqrt{16}*\sqrt{218}=4\sqrt{218}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(48)-4\sqrt{218}}{2*4}=\frac{-48-4\sqrt{218}}{8} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(48)+4\sqrt{218}}{2*4}=\frac{-48+4\sqrt{218}}{8} $
| 12x-3x=60 | | 4c/10=9/5 | | 6f+4/2=14 | | X^2-5x-12=24 | | 3b+6=b+3 | | 0.835x=11.42 | | p-7=3/5p+2/5p | | -6Y=x+12 | | 7h+2=12 | | -5(7-10b)=-2(-25b-9) | | (m-2)(m+5)=0 | | 4x-7+4x-7=6x | | (x+2x)-2=1/6*(x=2x) | | 3x-6+3x-6=4 | | x+17+x+17=x+27 | | 23+2x+23+2x=x+22 | | 4/5*x-12=1/5*x | | 2(2x+5)+15=7x+5-3x+20 | | 12x-3=3(4x+3) | | 12x-3=3(4x+) | | 2x-8+2x-8=x+8 | | 135x-150=15(9x-10) | | 25x+11=25x+24 | | 13q+17–q=15q+5 | | 1/2x-3/4-x=3/4 | | 3x+21-3=6(4x+7) | | x-0.25x=44 | | 5x=11+3x | | 1/2(x)+1/4=3/5 | | x-0.25x=26 | | 5x+(4x)=10+14 | | x(x-140)=-4500 |